ANALISIS KUALITAS WEBSITE BURSA EFEK INDONESIA DENGAN MENGGUNAKAN METODE GTMETRIX - Bija, Riartri Nanda; Talaohu, Alma Posyalam; Munandar, Agus (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
The Indonesia Stock Exchange is an institution that organizes and provides facilities for securities in Indonesia. This study aims to analyze the quality of how effective and efficient the Indonesia Stock Exchange's website is which can be accessed by all people to get information that is faster and updated for users. Website performance measurement testing is carried out using website performance testing tools with GTMetrix, which can provide website scores and recommendations to improve the performance of the Indonesia Stock Exchange website and speedtest.net is used to measure the internet speed of computer devices by conducting analysis. The results of testing the Indonesia Stock Exchange's website were obtained using GTmetrix to produce an overall score which showed that the Indonesia Stock Exchange's website reached grade A with a green color indicating a percentage of 91%, indicating that the performance of the Indonesia Stock Exchange's website received a very good score. From the results of this performance, it can be concluded that the higher the percentage, the faster the website can be accessed.